2013
DOI: 10.1186/1477-5751-12-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal undernutrition does not alter Sertoli cell numbers or the expression of key developmental markers in the mid-gestation ovine fetal testis

Abstract: BackgroundThe aim of this study was to determine the effects of maternal undernutrition on ovine fetal testis morphology and expression of relevant histological indicators. Maternal undernutrition, in sheep, has been reported, previously, to alter fetal ovary development, as indicated by delayed folliculogenesis and the altered expression of ovarian apoptosis-regulating gene products, at day 110 of gestation. It is not known whether or not maternal undernutrition alters the same gene products in the day 110 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The lack of effect upon Sertoli, germ and interstitial cells is in contrast to studies that reported a reduction in the number of Sertoli cells in newborn lambs undernourished in utero during the second trimester of gestation (Bielli et al 2002;Kotsampasi et al 2009) but concurs with studies that excised the testis at a fetal endpoint (Da Silva et al 2003;Andrade et al 2013).…”
Section: Testis Histologysupporting
confidence: 79%
“…The lack of effect upon Sertoli, germ and interstitial cells is in contrast to studies that reported a reduction in the number of Sertoli cells in newborn lambs undernourished in utero during the second trimester of gestation (Bielli et al 2002;Kotsampasi et al 2009) but concurs with studies that excised the testis at a fetal endpoint (Da Silva et al 2003;Andrade et al 2013).…”
Section: Testis Histologysupporting
confidence: 79%
“…The single bovine study shows FSH levels and testis volume were increased in the bull calf by first-trimester protein restriction (Sullivan et al 2010). In sheep, when endpoints were assessed in mid-pregnancy, the consensus is that neither maternal undernutrition nor reduced fetal nutrient supply affect Sertoli cell number, the number of seminiferous cords or basal pituitary gonadotrophin secretion (Rae et al 2002b;Andrade et al 2013). However, in the newborn lamb, the number of seminiferous cords and Sertoli cells was reduced following maternal undernutrition from mid-pregnancy onwards and was associated with a modest reduction in birthweight (12% reduction) relative to the adequately nourished control group (Bielli et al 2002).…”
Section: Female Offspring: Cattlementioning
confidence: 99%
“…Forty images (x630 magni cation) were taken of each vimentin immunostained testis, 10 from each 'compass' pole. This was deemed representative of the testis section 28 . For each image, the tubule area (pixels) and all Sertoli cells were counted.…”
Section: Sertoli Cell Number Quanti Cationmentioning
confidence: 99%
“…East (p≤0.001) and East Midlands (p≤0.01). Copenhagen also had signi cantly less PCNA staining than the South East (p≤0.05).Regional variation in testicular chemical pro lesThe chemical concentrations of diethyl hexyl phthalate (DEHP), sum of polychlorinated biphenyl congeners (PCB:28, 52, 101, 118, 138, 153, 180) and sum of polybrominated diethyl ether congeners (PBDE: 28, 47, 99, 100, 153, 154, 183) found in the testes of dogs living in ve different geographical regions are illustrated in gure 6. A signi cant difference in chemical pro le by region was observed (p≤0.01).…”
mentioning
confidence: 99%